2019
DOI: 10.1155/2019/4920647
|View full text |Cite
|
Sign up to set email alerts
|

Central Tendon-Splitting Approach and Double Row Suturing for the Treatment of Insertional Achilles Tendinopathy

Abstract: Background. To assess the clinical outcomes of central tendon-splitting approach and double row anchor suturing for the treatment of insertional Achilles tendinopathy. Methods. 28 patients (28 feet) diagnosed with insertional Achilles tendinopathy were included in this study. The inclusions were symptom of hindfoot pain around the insertion of the Achilles tendon, radiographic demonstration of calcification, or degeneration of the Achilles tendon, showing no symptom improvement even after standard nonsurgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…At the 7-year follow-up, 96% of the patients were pain free. Zhuang et al [15]reported that the central tendon-splitting approach was an effective surgical method for the treatment of Achilles tendon disease. However, there are no reports on reconstructing the footprint of the Achilles tendon on the calcaneus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the 7-year follow-up, 96% of the patients were pain free. Zhuang et al [15]reported that the central tendon-splitting approach was an effective surgical method for the treatment of Achilles tendon disease. However, there are no reports on reconstructing the footprint of the Achilles tendon on the calcaneus.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with severe ossi cation of the distal insertion of the Achilles tendon, it is often necessary to detach the tendon from the calcaneus, remove the heterotopic ossi cation, and then reattach the tendon to the calcaneus [12]. Reports on patient recovery and clinical effects vary greatly, and patients are often greatly delayed in their return to sports [13][14][15]. The insertion of the Achilles tendon is commonly reconstructed with a single or double row of anchors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the identification of the pain-causing pathology is often difficult, open debridement of all pathologies is regularly performed. 1,7,9,15,26,27,32,36,39 Open debridement necessitates extensile approaches to allow sufficient exposure to address all pathologies present. 1,9,10,27,32,39 In case of a dorsal spur, a (partial) detachment of the Achilles tendon might be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies reporting predominantly on the outcome of the surgical treatment do not perform any further analysis of complication rates and are limited by small sample sizes. 6,10,11,15,18,23,[25][26][27]30,32,[36][37][38][39] Our hypothesis was that the extent of the surgical procedure would influence complication rates. Therefore, the aim of this study was to assess the complication rate and possible influencing factors following the midline-incision trans-Achilles approach (MITA) for IAT.…”
Section: Introductionmentioning
confidence: 99%